The Evaluatıon Of The Ratıo Of The Posterıor-Anterıor Facıal Heıghts In Indıvıduals Wıth Normal Occlusıon - Emel Seren (Galenos Yayinevi, 1990)
In this research conducted on a group of 26 females and 33 males with normal dental and skeletal occlusion the posterior and facialheight mean values, the ratio between their, the differances in the mean values according to the sexes were found out and the relationship of these variables with the Y axis angle was examined. According to this research, the mean value of the posterior facial heights in females in the Turkish community was 81.42 ∓ 5.8 the mean value of the anterior facial height 120.19 ∓ 6.02: the mean value of the FHR was 67.98 ∓ 3.23 Jn males respectively 83.73 ∓ 6.3, 127.70 ∓ 6.9, 69.53 ∓ 4.3'The mean value differences among thes sexes the correlation coefficients between posterior and anterior facial heights and posterio facial height with FHR also found meaningful. Besides, a significant negative correlation was found between the Y axis angle and the posterior facial height only in females.